Structures and Role of the Intermediate Phases on the Crystallization of BaTiO(3) from an Aqueous Synthesis Route - Bakken, Kristine (ACS Omega, 2021)
[Image: see text] Carbonate formation is a prevailing challenge in synthesis of BaTiO(3), especially through wet chemical synthesis routes. In this work, we report the phase evolution during thermal annealing of an aqueous BaTiO(3) precursor solution, with a particular focus on the structures and role of intermediate phases forming prior to BaTiO(3) nucleation. In situ infrared spectroscopy, in situ X-ray total scattering, and transmission electron microscopy were used to reveal the decomposition, pyrolysis, and crystallization reactions occurring during thermal processing. Our results show that the intermediate phases consist of nanosized calcite-like BaCO(3) and BaTi(4)O(9) phases and that the intimate mixing of these along with their metastability ensures complete decomposition to form BaTiO(3) above 600 °C. We demonstrate that the stability of the intermediate phases is dependent on the processing atmosphere, where especially enhanced CO(2) levels is detrimental for the formation of phase pure BaTiO(3).